2014
DOI: 10.12691/jfnr-2-8-15
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Tea Polyphenols on the Formation of Advanced Glycation End Products (AGEs) <i>in vitro</i> and <i>in vivio</i>

Abstract: The effects of tea polyphenols (TP) on the formation of advanced glycation end products (AGEs) were investigated using glutamicacid -glucose and BSA -glucose model systems at 90°C and 37°C, respectively. The spectral characteristics of glycation products were measured. Additionally, a type 1 diabetesmellitus (DM) animal model of Kunming mice by injecting streptozocin (STZ) was used to study the formation of AGEs in vivo. Tea polyphenols (TP) were given to mice at a dose of 200mg/kg bodyweight continuously for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…In addition, a cookie model fortified with five selected dietary polyphenols (naringenin, quercetin, epicatechin, chlorogenic acid, and rosmarinic acid) showed inhibition against the formation of glyoxal and total fluorescent AGEs, especially those fortified with quercetin [ 142 ]. Additionally, streptozocin-induced type 1 diabetes in mice was used to study the formation of AGEs in vivo [ 143 ]. Tea polyphenols were given to mice daily, at a dose of 200 mg/kg of bodyweight for 8 weeks, and showed that the formation of AGEs decreased in a dose-dependent manner with increasing doses of tea polyphenols [ 143 ].…”
Section: Phenolic Compounds and Their Effect On Dicarbonyl Compounds ...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a cookie model fortified with five selected dietary polyphenols (naringenin, quercetin, epicatechin, chlorogenic acid, and rosmarinic acid) showed inhibition against the formation of glyoxal and total fluorescent AGEs, especially those fortified with quercetin [ 142 ]. Additionally, streptozocin-induced type 1 diabetes in mice was used to study the formation of AGEs in vivo [ 143 ]. Tea polyphenols were given to mice daily, at a dose of 200 mg/kg of bodyweight for 8 weeks, and showed that the formation of AGEs decreased in a dose-dependent manner with increasing doses of tea polyphenols [ 143 ].…”
Section: Phenolic Compounds and Their Effect On Dicarbonyl Compounds ...mentioning
confidence: 99%
“…Additionally, streptozocin-induced type 1 diabetes in mice was used to study the formation of AGEs in vivo [ 143 ]. Tea polyphenols were given to mice daily, at a dose of 200 mg/kg of bodyweight for 8 weeks, and showed that the formation of AGEs decreased in a dose-dependent manner with increasing doses of tea polyphenols [ 143 ].…”
Section: Phenolic Compounds and Their Effect On Dicarbonyl Compounds ...mentioning
confidence: 99%